55.7k views
1 vote
-62+[|9-36|÷6(2)-7] Evaluate the following expression

User Stundji
by
5.3k points

1 Answer

4 votes

Answer:

-60

Explanation:

Simplify the following:

-62 + (abs(9 - 36) 2)/6 - 7

2/6 = 2/(2×3) = 1/3:

-62 + abs(9 - 36)/3 - 7

9 - 36 = -27:

-62 + abs(-27)/3 - 7

Since -27<=0, then abs(-27) = 27:

-62 + 27/3 - 7

The gcd of 27 and 3 is 3, so 27/3 = (3×9)/(3×1) = 3/3×9 = 9:

-62 + 9 - 7

-62 + 9 - 7 = -60:

Answer: -60

User Ulmangt
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.